Very valentine eaudiobook - Trigiani, Adriana (Valentine Trilogy, 2009)
"Sex and the City meets Moonstruck....Sly, sensual, and dripping in style." —People Poignant, funny, warm, and red hot, Very Valentine is a wonderful treat for Adriana Trigiani fans—a "delightful" (Boston Globe), "romance-soaked novel" (Marie Claire) from much adored playwright, screenwriter, documentary filmmaker, and New York Times bestselling author of Lucia, Lucia; Rococo; and Big Stone Gap. The adventures of an extraordinary and unforgettable woman as she attempts to rescue her family's struggling shoe business and find love at the same time, Very Valentine sweeps the reader from the streets of Manhattan to the picturesque hills of la bella Italia. Already a national bestseller, here is a valentine from the incomparable Trigiani that you can take into your heart.